Gluing glue solution, composite diaphragm, preparation method of composite diaphragm and sodium ion battery

By using modified carbon materials and PVDF blend coatings on sodium ion battery separators and building composite nanofiber membranes with electrospinning technology, the problems of insufficient thermal stability and liquid absorption and liquid retention of the existing separators are solved, and the cycle life and safety performance of the battery are significantly improved.

CN119581791AActive Publication Date: 2025-03-07JIANGSU ZOOLNASM ENERGY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510131373.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-06
Publication Date
2025-03-07
Estimated Expiration
2045-02-06

AI Technical Summary

Technical Problem

The existing sodium ion battery separators have poor thermal stability and poor liquid retention when contacting high dielectric constant electrolyte, which affects the cycle life and safety of the battery.

Method used

The glue coating solution is prepared by blending modified carbon materials and polyvinylidene fluoride (PVDF), and a composite nanofiber membrane is constructed through electrospinning technology, and the modified carbon materials and PVDF blend coating is coated to form a composite separator.

Benefits of technology

It improves the thermal stability, mechanical strength and the wettability of the electrolyte, reduces the interface reaction resistance and temperature rise of the battery cell, and improves the cycle life and safety performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581791A_ABST
    Figure CN119581791A_ABST
Patent Text Reader

Abstract

The invention relates to the field of sodium-ion batteries, in particular to a coating glue solution, a composite diaphragm, a preparation method of the composite diaphragm and a sodium-ion battery. The gluing liquid comprises the following components in percentage by mass: 3%-5% of a modified carbon material, 75%-85% of an organic solvent and 10%-22% of polyvinylidene fluoride; the modified carbon material is prepared by coating the surface of a carbon material with sodium propargyl sulfonate, and the mass ratio of the carbon material to the sodium propargyl sulfonate is (0.2-0.5): (2-5). The modified carbon material is introduced into the gluing liquid, a conductive network is formed on the surface of the diaphragm, electron transmission is promoted, and the interface reaction resistance of a battery cell is reduced; the heat dissipation performance of the carbon material is utilized, so that the safety of the battery cell is improved; and the coating contains polyvinylidene fluoride, so that the binding power between the diaphragm and the positive and negative electrodes is increased, the diaphragm has good wettability and moisture retention on electrolyte, and the cycle life of a battery cell is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of sodium ion batteries, and in particular to a coating glue solution, a composite diaphragm, a method for preparing a composite diaphragm, and a sodium ion battery. Background Art

[0002] Energy shortages caused by the extensive use of chemical fuels have become a global focus, so new energy sources need to be developed to solve the energy and environmental crises. Sodium-ion batteries have been widely studied due to their long service life, high safety, low theoretical cost and abundant resources. In sodium-ion batteries, the diaphragm plays the role of physically isolating the positive and negative electrodes. It not only physically isolates the positive and negative electrodes to prevent direct contact and short circuits, but also ensures the wettability of the electrolyte, allowing the solvated sodium ions to pass quickly. The selection and performance of the diaphragm directly affect the overall performance of the sodium-ion battery, including energy density, cycle life, rate performance and safety performance.

[0003] At present, the commonly used diaphragms on the market are polyolefin diaphragms or coated diaphragms, which have the disadvantages of poor thermal stability, poor liquid absorption and retention, and low porosity, especially when in contact with electrolytes with high dielectric constants such as cyclic carbonates. Its wettability is poor, which will affect the cycle life and safety of the battery. In the coated diaphragm, both the coating slurry and the substrate play a vital role. The substrate provides basic mechanical strength and chemical stability. The coating slurry can not only provide thermal stability, mechanical strength, and chemical stability, but also improve the wettability of the electrolyte and the charge and discharge performance of the battery. Therefore, the coating slurry is an important factor influencing the excellent performance of the diaphragm. Therefore, it is necessary to provide an improved coating slurry and diaphragm material to improve the working performance of sodium ion batteries. Summary of the invention

[0004] In order to solve the above technical problems, the present application proposes a coating glue solution, a composite diaphragm, a method for preparing the composite diaphragm and a sodium ion battery.

[0005] The specific technical solutions of the present invention are as follows: On the one hand, the embodiment of the present application provides a coating glue solution, which includes: 3% to 5% by weight of a modified carbon material, 75% to 85% by weight of an organic solvent, and 10% to 22% by weight of polyvinylidene fluoride; The modified carbon material is prepared by coating sodium propargyl sulfonate on the surface of the carbon material. In the modified carbon material, the mass ratio of the carbon material to the sodium propargyl sulfonate is (0.2-0.5): (2-5).

[0006] In a possible implementation manner, the carbon material includes one or more of multi-walled carbon nanotubes, graphene, and conductive carbon black.

[0007] In a possible implementation manner, the organic solvent is any one of N-methylpyrrolidone, N,N-dimethylformamide and dimethyl sulfoxide.

[0008] On the other hand, the present application also provides a method for preparing a coating glue solution, the preparation method comprising: Dissolving 2 g to 5 g of sodium propargyl sulfonate in a preset volume of deionized water to obtain a sodium propargyl sulfonate solution; 0.2 g to 0.5 g of carbon material is added to a sodium propargyl sulfonate solution, and a mixed solution is obtained after dispersion and stirring, and the mixed solution is filtered, washed and dried to obtain a modified carbon material; The modified carbon material is added into an organic solvent, and a modified carbon dispersion solution is obtained after dispersion treatment and stirring treatment; polyvinylidene fluoride is added into the modified carbon dispersion solution, and a coating adhesive solution is obtained after stirring treatment.

[0009] On the other hand, an embodiment of the present application further provides a composite diaphragm, the composite diaphragm comprising a composite nanofiber membrane and a diaphragm coating coated on at least one side of the composite nanofiber membrane; The composite nanofiber membrane is obtained by film-forming a sulfide solid electrolyte and a polymer; The diaphragm coating is obtained by coating the above-mentioned coating glue solution, and the thickness of the diaphragm coating is 2μm to 4μm.

[0010] On the other hand, the present invention also provides a method for preparing a composite membrane, the method comprising: adding a sulfide solid electrolyte into an organic solvent and dispersing the sulfide solid electrolyte to obtain a sulfide solid electrolyte dispersion; Adding the polymer into the sulfide solid electrolyte dispersion, stirring and treating to obtain a composite spinning solution; Performing film-forming treatment on the composite spinning solution by electrospinning, and obtaining a composite nanofiber membrane after drying; The above-mentioned adhesive solution is coated on at least one side of the composite nanofiber membrane, and a composite diaphragm is obtained after drying.

[0011] In a possible implementation manner, in the composite spinning solution, the mass proportion of the sulfide solid electrolyte is 3% to 5%, the mass proportion of the organic solvent is 75% to 85%, and the mass proportion of the polymer is 10% to 22%.

[0012] In a possible embodiment, the sulfide solid electrolyte is Na3PS4, Na 11 Sn2PS2, Na3SbS4, Na 11.5 Sn2Sb 0.5 Ti 0.5 S 12 、Na 2.95Sb 0.95 W 0.05 S 3.9 O 0.1 At least one of the following; the diameter of the sulfide solid electrolyte is 300nm to 500nm.

[0013] In a possible implementation, the polymer is one of polyethersulfone, polyetherketone, polyethylene terephthalate, polyamide, polyvinylidene fluoride, polybenzimidazole, polyphenylene sulfide and polyimide.

[0014] In a possible implementation manner, the organic solvent is any one of N-methylpyrrolidone, N,N-dimethylformamide and dimethyl sulfoxide.

[0015] In a possible implementation manner, the composite nanofiber membrane has a porosity of 70% to 90% and a thickness of 10 μm to 50 μm.

[0016] On the other hand, an embodiment of the present application further provides a sodium ion battery, which includes the above-mentioned composite diaphragm.

[0017] Based on the above technical solution, the present invention has at least the following beneficial effects: 1. For the coating glue solution, the present application introduces modified carbon material into the coating glue solution, and the modified carbon material is prepared by coating sodium propargyl sulfonate (Pys) on the surface of the carbon material. The dispersion of the carbon material in the coating glue solution is improved by coating sodium propargyl sulfonate, thereby avoiding the local charge difference caused by the agglomeration of the carbon material, and ensuring that the introduction of the carbon material will not have a negative impact on the cycle performance and impedance of the battery. At the same time, the coating glue solution contains polyvinylidene fluoride, which can increase the bonding force between the diaphragm and the positive and negative electrodes after being used for diaphragm coating, and has good wettability and moisture retention to the electrolyte, which can improve the cycle life of the battery cell.

[0018] 2. For the composite diaphragm, the present application first constructs a composite nanofiber membrane by electrostatic spinning, and the fiber membrane prepared by electrostatic spinning has a large porosity, which is conducive to the passage of sodium ions. In the composite nanofiber membrane, the use of sulfide as a solid electrolyte can utilize its own high ionic conductivity and the good wettability of cyclic carbonate to reduce the polarization internal resistance of the battery and improve the cycle life of the battery; then the above-mentioned glue coating glue is applied on the surface of the composite nanofiber membrane, so that a very small amount of modified carbon material is evenly loaded on the surface of the diaphragm, and the conductivity of the carbon material can be utilized to form a conductive network on the surface of the diaphragm to promote electron transmission, thereby reducing the interface reaction resistance of the battery, and utilizing the heat dissipation of the carbon material, under high rate charge and discharge, the heat is dispersed in time, thereby reducing the temperature rise and improving the safety of the battery; and the coating contains polyvinylidene fluoride, which can increase the bonding force between the diaphragm and the positive and negative electrodes, has good wettability and moisture retention to the electrolyte, and can improve the cycle life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the technical solutions and advantages in the embodiments of the present application or the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0020] Figure 1 It is a schematic flow chart of a method for preparing a coating adhesive solution provided in an embodiment of the present application.

[0021] Figure 2 It is a schematic flow chart of a method for preparing a composite diaphragm provided in an embodiment of the present application. DETAILED DESCRIPTION

[0022] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0023] It should be noted that the terms "first", "second", etc. in the specification and claims of the embodiments of the present application and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the embodiments of the present application described here can be implemented in an order other than those illustrated or described here. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present embodiment, unless otherwise stated, the meaning of "plurality" is two or more. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions.

[0024] The embodiments of the present application are described below in combination with the above technical solutions.

[0025] The embodiment of the present application provides a coating glue solution, which includes: 3-5% by weight of a modified carbon material, 75-85% by weight of an organic solvent, and 10-22% by weight of polyvinylidene fluoride; The modified carbon material is prepared by coating sodium propargyl sulfonate on the surface of the carbon material. In the modified carbon material, the mass ratio of the carbon material to the sodium propargyl sulfonate is (0.2-0.5): (2-5).

[0026] Illustratively, in the above-mentioned coating glue, the mass ratio of modified carbon material, organic solvent and polyvinylidene fluoride is 3% to 5%: 75% to 85%: 10% to 22%, excluding other components, and the total mass proportion of the three reaches 100%.

[0027] The modified carbon material is obtained by coating the surface of the carbon material with sodium propargyl sulfonate. In the modified carbon material, the mass ratio of the carbon material to the sodium propargyl sulfonate is (0.2-0.5): (2-5).

[0028] It should be noted that the coating glue solution provided in the embodiments of the present application does not require a dispersant, which may bring advantages such as cost reduction, simplification of the coating glue solution preparation process, reduction of variables in the production process, and thus improvement of battery product quality.

[0029] In some embodiments, the carbon material includes one or more of multi-walled carbon nanotubes, graphene, and conductive carbon black.

[0030] For example, one or more of multi-walled carbon nanotubes, graphene, and conductive carbon black are used as carbon material raw materials, because these types of carbon materials have good thermal conductivity and heat dissipation, which help to improve the performance of the diaphragm.

[0031] In some embodiments, the organic solvent is any one of N-methylpyrrolidone, N,N-dimethylformamide and dimethyl sulfoxide.

[0032] For example, the modified carbon material and PVDF are blended by dissolving in an organic solvent. The organic solvent modification can increase the compatibility between the modified carbon material and PVDF, thereby improving the interfacial bonding strength between the two.

[0033] In the embodiment of the present application, polyvinylidene fluoride (PVDF) and modified carbon materials are doped and blended to prepare a coating glue solution. The coating glue solution is used for diaphragm coating, so that the surface of the diaphragm can be coated with the coating glue solution containing modified carbon materials, and the carbon material can be modified to be evenly dispersed in the coating layer, thereby utilizing the conductivity of the carbon material to form a conductive network on the surface of the diaphragm, promoting electron transmission, and reducing the interface reaction resistance of the battery cell. At the same time, the carbon material has heat dissipation properties, so that heat can be dispersed in time under high-rate charge and discharge, reducing temperature rise and improving the safety of the battery cell. The modified carbon material is prepared by coating the surface of the carbon material with sodium propargyl sulfonate (Pys) through π-π conjugation, which improves the dispersibility of the carbon material, avoids the agglomeration of the carbon material in the coating glue solution, and makes a very small amount of carbon material evenly loaded on the surface of the diaphragm, avoiding the agglomerated carbon material from causing uneven distribution of the load on the surface of the diaphragm, thereby causing local charge differences, affecting the cycle performance, and increasing impedance. The coating layer contains PVDF, which can increase the adhesion between the diaphragm and the positive and negative electrodes, has good wettability and moisture retention to the electrolyte, and can increase the cycle life of the battery cell.

[0034] On the other hand, Figure 1 As shown, on the other hand, the embodiment of the present application also provides a method for preparing a coating glue solution, the preparation method comprising: S101: dissolving 2 g to 5 g of sodium propargyl sulfonate in a preset volume of deionized water to obtain a sodium propargyl sulfonate solution; S103: adding 0.2 g to 0.5 g of carbon material to a sodium propargyl sulfonate solution, dispersing and stirring to obtain a mixed solution, filtering, washing and drying the mixed solution to obtain a modified carbon material; S105: adding the modified carbon material into an organic solvent, dispersing and stirring to obtain a modified carbon dispersion solution; S107: adding polyvinylidene fluoride into the dispersed solution of modified carbon, and stirring to obtain a coating adhesive solution.

[0035] Exemplarily, the preparation process of the coating glue solution includes: (1) Preparation of modified carbon materials: S101: Dissolve 2 g to 5 g of sodium propargyl sulfonate (Pys) in a preset volume of deionized water to obtain the sodium propargyl sulfonate solution.

[0036] Preferably, the preset volume is 100±5 ml, preferably 100 ml, allowing a certain error range.

[0037] S103: adding 0.2g to 0.5g of carbon material to the sodium propargyl sulfonate solution, dispersing and stirring to obtain a mixed solution, filtering, washing and drying the mixed solution to obtain a modified carbon material; wherein the carbon material includes one or more of multi-walled carbon nanotubes, graphene, and conductive carbon black.

[0038] Specifically, it can be understood that the first preset weight can be any value between 2g and 5g, and can be 2, 3, 4, 5, etc. The first preset weight can be any value between 0.2g and 0.5g, and can be 0.2, 0.3, 0.4, 0.5, etc.

[0039] Optionally, the above-mentioned dispersion treatment can be ultrasonic dispersion, and the time is 1h to 2h. Specifically, it can be understood that the dispersion time can be any point value between 1h and 2h, and illustratively, it can be 1, 1.5, 1.8, 2, etc.

[0040] Optionally, the stirring time is 1 h to 6 h. Specifically, it can be understood that the stirring time can be any point value between 1 h and 6 h. For example, it can be 1, 1.5, 2, 3, etc.

[0041] It should be noted that the specific conditions for filtering, washing and drying are not limited and can be performed according to existing technologies.

[0042] (2) Preparation of glue coating solution: S105: adding the modified carbon material into an organic solvent, dispersing and stirring to obtain a modified carbon dispersion solution. The organic solvent is any one of N-methylpyrrolidone, N,N-dimethylformamide and dimethyl sulfoxide.

[0043] Exemplarily, the above-mentioned dispersion treatment and stirring treatment can be carried out by vacuum stirring, and the specific conditions can be vacuum stirring for 1 hour to 6 hours at a vacuum degree of -0.08 MPa to -0.1 MPa. The vacuum degree can be any point value between -0.08 MPa and -0.1 MPa, such as -0.08, -0.085, -0.09, and -0.1. The stirring time can be any point value between 1 hour and 6 hours, and can be 1, 1.5, 2, 3, and the like.

[0044] S107: adding polyvinylidene fluoride into the dispersed solution of modified carbon, and stirring to obtain a coating adhesive solution.

[0045] For example, polyvinylidene fluoride (PVDF) is added to a dispersed solution of modified carbon, and the solution is stirred to obtain a coating adhesive.

[0046] Optionally, the stirring treatment may be performed under vacuum stirring, and the vacuum stirring conditions are: vacuum stirring for 6 to 12 hours at a vacuum degree of -0.08 MPa to -0.1 MPa. Specifically, the vacuum degree may be any value between -0.08 MPa and -0.1 MPa, such as -0.08, -0.085, -0.09, and -0.1. The stirring time may be any value between 6 hours and 12 hours, and may be 6, 7, 10, 12, and the like, for example.

[0047] In the embodiment of the present application, the carbon material is first modified by sodium propargyl sulfonate (Pys) to prepare a modified carbon material, and then the modified carbon material is mixed with PVDF to prepare a coating glue solution. The above-mentioned coating glue solution is used for diaphragm coating, so that the surface of the diaphragm can be coated with the coating glue solution containing the modified carbon material, and the modified carbon material can be evenly dispersed in the coating layer. The conductivity of the carbon material can form a conductive network on the surface of the diaphragm, promote electron transmission, and reduce the interface reaction resistance of the battery cell. At the same time, the carbon material has heat dissipation. Under high-rate charge and discharge, heat can be dispersed in time, temperature rise can be reduced, and the safety of the battery cell can be improved. And the modified carbon material is prepared by coating sodium propargyl sulfonate (Pys) on the surface of the carbon material through π-π conjugation, which improves the dispersibility of the carbon material, avoids the agglomeration of the carbon material in the coating glue solution, and makes a very small amount of carbon material evenly loaded on the surface of the diaphragm, avoiding the agglomerated carbon material from causing uneven distribution of the load on the surface of the diaphragm, thereby causing local charge differences, affecting the cycle performance, and increasing impedance. The coating layer contains PVDF, which can increase the adhesion between the diaphragm and the positive and negative electrodes, has good wettability and moisture retention to the electrolyte, and can increase the cycle life of the battery cell.

[0048] On the other hand, an embodiment of the present application further provides a composite membrane, the composite membrane comprising a composite nanofiber membrane and a membrane coating coated on at least one side of the composite nanofiber membrane; The composite nanofiber membrane is obtained by film-forming a sulfide solid electrolyte and a polymer; The diaphragm coating is obtained by coating the above-mentioned coating glue solution, and the thickness of the diaphragm coating is 2μm to 4μm.

[0049] In the embodiment of the present application, sulfide solid electrolyte and polymer are used as raw materials for composite nanofiber membrane, and a coating glue prepared by blending modified carbon material and PVDF is coated on the composite nanofiber membrane. The conductivity and heat dissipation of carbon material are utilized to form a conductive network on the surface of the diaphragm, promote electron transmission, and reduce the interface reaction resistance of the battery cell. Under high rate charge and discharge, heat can be dispersed in time to reduce temperature rise and improve the safety of the battery cell. In addition, the high ionic conductivity (>10 -3 S / cm), good mechanical ductility, good interface contact with the electrode, large specific surface area, high surface energy, etc., adding sulfide solid electrolyte as an inorganic filler into the polymer matrix can greatly improve the impact strength, tensile strength, heat deformation temperature, etc. of the diaphragm, and the sulfide solid electrolyte has the characteristic of good wettability with cyclic carbonate, which can reduce the polarization internal resistance of the battery cell and increase the cycle life of the battery cell, and can improve the overall ionic conductivity and liquid retention capacity of the diaphragm.

[0050] On the other hand, Figure 2As shown, the present application embodiment also provides a method for preparing a composite diaphragm, the method comprising: S201: adding a sulfide solid electrolyte into an organic solvent to disperse the sulfide solid electrolyte to obtain a sulfide solid electrolyte dispersion; S203: adding a polymer to a sulfide solid electrolyte dispersion, and stirring to obtain a composite spinning solution; S205: performing film-forming treatment on the composite spinning solution by electrospinning, and obtaining a composite nanofiber membrane after drying; S207: coating the above-mentioned adhesive solution on at least one side of the composite nanofiber membrane, and drying the composite membrane.

[0051] Exemplarily, the preparation process of the composite membrane may include the following steps: S201: adding a sulfide solid electrolyte into an organic solvent and dispersing the sulfide solid electrolyte to obtain a sulfide solid electrolyte dispersion.

[0052] In some embodiments, the sulfide solid electrolyte is Na3PS4, Na 11 Sn2PS2, Na3SbS4, Na 11.5 Sn2Sb 0.5 Ti 0.5 S 12 、Na 2.95 Sb 0.95 W 0.05 S 3.9 O 0.1 At least one of the following; the diameter of the sulfide solid electrolyte is 300nm to 500nm.

[0053] In some embodiments, the organic solvent is any one of N-methylpyrrolidone, N,N-dimethylformamide and dimethyl sulfoxide.

[0054] Optionally, the dispersion treatment may be ultrasonic dispersion for 3 hours to 6 hours. Specifically, the dispersion time may be any point value between 3 hours and 6 hours, for example, 3, 4, 5, 6, etc.

[0055] It should be noted that the diameter selection of the sulfide solid electrolyte is related to the thickness of the final synthesized composite nanofiber membrane. Different sulfide solid electrolytes will also affect the performance of sodium-ion batteries. The specific material and diameter of the sulfide solid electrolyte can be selected according to the final application of the composite diaphragm.

[0056] S203: adding the polymer into the sulfide solid electrolyte dispersion, and stirring to obtain a composite spinning solution.

[0057] In some embodiments, the polymer is one of polyethersulfone (PES), polyetherketone (PEEK), polyethylene terephthalate (PET), polyamide (PA), polyvinylidene fluoride (PVDF), polybenzimidazole (PBI), polyphenylene sulfide (PPS), and polyimide (PI).

[0058] Optionally, the stirring time is 12 hours to 24 hours. Specifically, the dispersion time can be any point value in the range of 12 hours to 24 hours, for example, it can be 12, 15, 15, 24, etc.

[0059] It should be noted that in the composite solution, the mass proportion of the sulfide solid electrolyte is 3% to 5%, the mass proportion of the organic solvent is 75% to 85%, and the mass proportion of the polymer is 10% to 22%. The total mass proportion of the three must meet 100%.

[0060] S205: performing film-forming treatment on the composite spinning solution by electrostatic spinning, and obtaining a composite nanofiber membrane after drying.

[0061] For example, electrospinning is an advanced nanofiber manufacturing technology that uses a high-voltage electrostatic field to spray polymer solutions to form extremely fine fibers. These fibers have shown a wide range of application potentials in the fields of medicine, filtration, energy, and environment due to their high specific surface area and porous structure. This technology can precisely control the diameter and structure of the fibers, providing a powerful tool for the development of new high-performance materials.

[0062] In the embodiment of the present application, the composite spinning prepared in the above S201 to S202 is subjected to film-forming treatment by electrostatic spinning technology to obtain a composite spinning nanofiber membrane.

[0063] Optionally, the conditions for electrospinning are as follows: a micropump push speed of 0.02 m / min to 1.0 m / min, a syringe needle diameter of 0.025 cm to 0.05 cm, a syringe diameter of 2 cm, a receiving roller speed of 3 m / min to 8 m / min, a needle sweep speed of 5 cm / min to 10 cm / min, a voltage of 15 kV to 25 kV, a distance from the syringe needle to the receiving roller of 10 cm to 20 cm, and an electrospinning time of 5 h to 10 h.

[0064] In some embodiments, the composite nanofiber membrane has a porosity of 70% to 90% and a thickness of 10 μm to 50 μm.

[0065] Specifically, it can be understood that the porosity of the composite nanofiber membrane synthesized by the above-mentioned steps S201 to S205 can be any point value in the range of 70% to 90%, and can be 70%, 75%, 80%, 85%, 90%, etc. for example. The thickness of the composite nanofiber membrane can be any point value in the range of 10 μm to 50 μm, and can be 10 μm, 20 μm, 30 μm, 40 μm, and 50 μm for example. The specific thickness and porosity can be adjusted based on the mass proportion of the three raw materials of the sulfide solid electrolyte, the organic solvent and the polymer in the composite spinning solution, and based on the conditions of electrospinning.

[0066] S207: coating the above-mentioned adhesive solution on at least one side of the composite nanofiber membrane, and drying the composite membrane.

[0067] Exemplarily, the above-mentioned adhesive coating solution is coated on at least one side of the composite nanofiber membrane, that is, the membrane coating is coated, and the composite membrane is obtained after drying.

[0068] Optionally, the thickness of the diaphragm coating is 2 μm to 4 μm, that is, the coating thickness is 2 μm to 4 μm. Specifically, it can be understood that the coating thickness can be any point value between 2 μm and 4 μm, for example, it can be 2 μm, 3 μm, 4 μm, etc.

[0069] Optionally, the drying temperature is 80° C. to 90° C. Specifically, it can be understood that the drying temperature can be any point value between 80° C. and 90° C., for example, it can be 80° C., 82° C., 84° C., 86° C., 88° C., 90° C., etc.

[0070] Optionally, the coating method may be gravure roller coating, dip coating, narrow coating, spray coating, etc.

[0071] In the embodiment of the present application, a composite spinning solution is first prepared by using a sulfide solid electrolyte and a polymer, and then the composite spinning solution is prepared into a composite nanofiber membrane by electrostatic spinning technology, and then the coating glue is coated on the composite nanofiber membrane to obtain a composite diaphragm. The composite diaphragm has the following advantages: 1. Sulfide solid electrolyte and polymer are used as raw materials for composite nanofiber membrane, and the composite nanofiber membrane is coated with a coating glue prepared by blending modified carbon material and PVDF, which makes full use of the conductivity and heat dissipation of carbon materials. It can not only form a conductive network on the surface of the diaphragm, promote electron transmission, and reduce the interfacial reaction resistance of the battery cell, but also disperse the heat in time under high rate charge and discharge, reduce the temperature rise, and improve the safety of the battery cell; 2. The coating layer contains PVDF, and the positive electrode of the battery uses PVDF adhesive, which will have a good bonding effect with the coating layer, can increase the bonding force between the diaphragm and the positive and negative electrode sheets, and has good wettability and moisture retention for the electrolyte.

[0072] 3. Sulfide solid electrolyte has high ionic conductivity (>10 -3 S / cm), good mechanical ductility, good interface contact with the electrode, large specific surface area, high surface energy and other advantages. The sulfide solid electrolyte is added to the polymer matrix as an inorganic filler, so that the impact strength, tensile strength, heat deformation temperature and other aspects of the composite nanofiber membrane are greatly improved. The sulfide solid electrolyte has the property of good wettability with cyclic carbonate, which can reduce the polarization internal resistance of the battery cell and increase the cycle life of the battery cell, and can improve the overall ionic conductivity and liquid retention capacity of the diaphragm.

[0073] 4. The composite nanofiber membrane prepared by electrospinning has good thickness uniformity and high porosity, which is conducive to the passage of sodium ions and can improve the liquid retention capacity of the membrane.

[0074] On the other hand, an embodiment of the present application also provides a sodium ion battery, comprising the above-mentioned composite diaphragm.

[0075] Optionally, the sodium ion battery also includes a negative electrode sheet, a sodium ion positive electrode sheet, and a sodium ion electrolyte, and is prepared into a sodium ion battery through processes such as rolling, die cutting, lamination, assembly, baking, liquid injection, standing, formation, and capacity separation.

[0076] The sodium ion battery provided by the embodiment of the present application has at least the following beneficial effects: 1. The modified carbon material is coated on the surface of the diaphragm so that the carbon material can be evenly dispersed in the coating layer, which promotes electron transmission and reduces the interfacial reaction resistance of the battery cell. At the same time, the carbon material has heat dissipation properties. Under high-rate charge and discharge, the heat can be dispersed in time, the temperature rise can be reduced, and the safety of the battery cell can be improved.

[0077] 2. The coating layer contains PVDF, which can increase the bonding force between the diaphragm and the positive and negative electrodes, has good wettability and moisture retention for the electrolyte, and can improve the cycle life of the battery cell.

[0078] 3. The composite nanofiber membrane is constructed by electrospinning. The composite nanofiber membrane prepared by electrospinning has a large porosity, which is conducive to the passage of sodium ions. The composite nanofiber membrane contains a sulfide solid electrolyte, which can utilize the high ionic conductivity and good wettability of the sulfide solid electrolyte with cyclic carbonate to reduce the polarization internal resistance of the battery cell and improve the cycle life of the battery cell.

[0079] The present application also provides a series of examples to further verify the implementation effects of the composite diaphragm and its preparation method, and the sodium ion battery in the technical solution of the present application. The implementation effects of the technical solution of the present application are described in detail below in combination with specific examples.

[0080] Embodiment 1: The present application provides a coating glue solution, and the specific preparation method includes: 1. Dissolve 2 g of sodium propargyl sulfonate (Pys) in 100 mL of deionized water to obtain a sodium propargyl sulfonate solution.

[0081] 2. Add 0.3 g of multi-walled carbon nanotubes to the sodium propargyl sulfonate solution, ultrasonically disperse for 1 hour and stir for 6 hours to obtain a mixed solution, filter the mixed solution, wash, and dry to obtain a modified carbon material.

[0082] 3. The modified carbon material was added to N,N-dimethylformamide (DMF) for dispersion, and vacuum stirred for 6 hours at a vacuum degree of -0.09 MPa to obtain a dispersed solution of modified carbon.

[0083] 4. Add polyvinylidene fluoride (PVDF) to the dispersed solution of modified carbon, and stir under vacuum at a vacuum degree of -0.09 MPa for 10 h to obtain a coating adhesive solution.

[0084] In the above process, the mass ratio of modified carbon material, organic solvent and polyvinylidene fluoride is 3%:75%:22%.

[0085] The present application provides a composite diaphragm, and the specific preparation method includes: 1. The sulfide solid electrolyte Na3PS4 with a diameter of 300 nm was ultrasonically dispersed in N,N-dimethylformamide (DMF) for 6 h to prepare a sulfide solid electrolyte dispersion.

[0086] 2. Dissolve polyethersulfone (PES) powder in sulfide solid electrolyte dispersion and stir for 24 hours to obtain a composite spinning solution.

[0087] Among them, the mass ratio of sulfide solid electrolyte, polymer and organic solvent is 0.5%:20%:79.5%.

[0088] 3. The composite spinning solution was made into a membrane by electrospinning, and dried at 80°C for 24 hours to obtain a composite nanofiber membrane. The electrospinning conditions were as follows: the micropump push speed was 0.06 m / min, the syringe needle diameter was 0.035 cm, the syringe diameter was 2 cm, the receiving roller speed was 6 m / min, the needle sweep speed was 7 cm / min, the voltage was 20 kV, the distance from the syringe needle to the receiving roller was 15 cm, and the electrospinning time was 8 hours.

[0089] The composite nanofiber membrane prepared by the above process had a porosity of 80% and a thickness of 24 μm.

[0090] 4. The coating glue solution is evenly coated on one side surface of the composite nanofiber membrane by a coating machine with a coating thickness of 3 μm, and dried at 85° C. to obtain a composite diaphragm.

[0091] The present application also provides a sodium ion battery, the specific preparation method of which includes: After the composite diaphragm, negative electrode sheet, sodium ion positive electrode sheet and sodium ion electrolyte are prepared, a sodium ion battery is prepared through processes such as rolling, die cutting, lamination, assembly, baking, liquid injection, standing, formation and capacity division.

[0092] Embodiment 2: The present application provides a coating glue solution, and the specific preparation method includes: 1. Dissolve 3 g of sodium propargyl sulfonate (Pys) in 100 mL of deionized water to obtain a sodium propargyl sulfonate solution.

[0093] 2. 0.2 g of graphene was added to the sodium propargyl sulfonate solution, ultrasonically dispersed for 1 h and stirred for 3 h to obtain a mixed solution, which was filtered, washed, and dried to obtain a modified carbon material.

[0094] 3. The modified carbon material was added to N-methylpyrrolidone (NMP) for dispersion, and vacuum stirred for 2 h at a vacuum degree of -0.08 MPa to obtain a dispersed solution of modified carbon.

[0095] 4. Add polyvinylidene fluoride (PVDF) to the first mixture, and stir under vacuum at a vacuum degree of -0.08 MPa for 6 hours to obtain a coating adhesive solution.

[0096] In the above process, the mass ratio of the modified carbon material, the organic solvent and the polyvinylidene fluoride is 4%:80%:16%.

[0097] The present application provides a composite diaphragm, and the specific preparation method includes: 1. The sulfide solid electrolyte Na3PS4 with a diameter of 300 nm was ultrasonically dispersed in N-methylpyrrolidone (NMP) for 3 h to prepare a sulfide solid electrolyte dispersion.

[0098] 2. Dissolve polyamide (PA) powder in sulfide solid electrolyte dispersion and stir for 12 hours to obtain a composite spinning solution.

[0099] Among them, the mass ratio of sulfide solid electrolyte, polymer and organic solvent is 0.3%:15%:84.7%.

[0100] 3. The composite spinning solution was made into a membrane by electrospinning, and dried at 60°C for 12 hours to obtain a composite nanofiber membrane. The conditions for electrospinning were: micropump push speed of 0.02m / min, syringe needle diameter of 0.025cm, syringe diameter of 2cm, receiving roller speed of 3m / min, needle sweep speed of 5cm / min, voltage of 15kV, distance from syringe needle to receiving roller of 10cm, and electrospinning time of 5h.

[0101] The composite nanofiber membrane prepared by the above process had a porosity of 70% and a thickness of 12 μm.

[0102] 4. The coating glue solution is evenly coated on one side surface of the composite nanofiber membrane by a coating machine with a coating thickness of 2 μm, and dried at 80° C. to obtain a composite diaphragm.

[0103] A sodium ion battery provided in this embodiment is prepared using the composite diaphragm obtained above, and the specific steps are consistent with those in the aforementioned embodiment 1, which will not be repeated here.

[0104] Embodiment 3: The present application provides a coating glue solution, and the specific preparation method includes: 1. Dissolve 5 g of sodium propargyl sulfonate (Pys) in 100 mL of deionized water to obtain a sodium propargyl sulfonate solution.

[0105] 2. Add 0.5 g of conductive carbon black into the mixed solution, ultrasonically disperse for 2 h and stir for 6 h to obtain a mixed solution. Filter, wash and dry the mixed solution to obtain a modified carbon material.

[0106] 3. Add the modified carbon material into dimethyl sulfoxide (DMSO) for dispersion, and stir under vacuum at a vacuum degree of -0.08 MPa to -0.1 MPa for 1 to 6 hours to obtain a dispersed solution of modified carbon.

[0107] 4. Add polyvinylidene fluoride (PVDF) to the dispersed solution of modified carbon, and stir under vacuum at a vacuum degree of -0.1 MPa for 12 h to obtain a coating adhesive solution.

[0108] In the above process, the mass ratio of the modified carbon material, the organic solvent and the polyvinylidene fluoride is 5%:85%:10%.

[0109] The present application provides a composite diaphragm, and the specific preparation method includes: 1. The sulfide solid electrolyte Na with a diameter of 500nm 2.95 Sb 0.95 W 0.05 S 3.9 O 0.1The sulfide solid electrolyte dispersion was prepared by placing it in dimethyl sulfoxide (DMSO) and ultrasonically dispersing it for 6 hours.

[0110] 2. Dissolve polybenzimidazole (PBI) powder in sulfide solid electrolyte dispersion and stir for 24 hours to obtain a composite spinning solution.

[0111] Among them, the weight ratio of sulfide solid electrolyte, polymer and organic solvent is 1%:20%:79%.

[0112] 3. The composite spinning solution was made into a membrane by electrospinning, and dried at 100°C for 24 hours to obtain a composite nanofiber membrane.

[0113] The conditions for electrospinning were as follows: micropump push speed of 1.0 m / min, syringe needle diameter of 0.05 cm, syringe barrel diameter of 2 cm, receiving roller speed of 8 m / min, needle sweep speed of 10 cm / min, voltage of 25 kV, distance from syringe needle to receiving roller of 20 cm, and electrospinning time of 10 h.

[0114] The composite nanofiber membrane prepared by the above process had a porosity of 90% and a thickness of 50 μm.

[0115] 4. The coating glue solution is evenly coated on one side surface of the composite nanofiber membrane by a coating machine with a coating thickness of 4 μm, and dried at 90° C. to obtain a composite diaphragm.

[0116] A sodium ion battery provided in this embodiment is prepared using the composite diaphragm obtained above, and the specific steps are consistent with those in the aforementioned embodiment 1, which will not be repeated here.

[0117] Comparative Example 1: This comparative example uses a commercial polyethylene diaphragm to prepare a sodium ion battery. This comparative example provides a sodium ion battery prepared using a commercial polyethylene diaphragm. The specific steps are consistent with those in the aforementioned Example 1 and are not described in detail here.

[0118] Comparative Example 2: In this comparative example, a PVDF coated diaphragm is used to prepare a sodium ion battery. A sodium ion battery provided in this comparative example is prepared using a commercial polyethylene diaphragm. The specific steps are consistent with those in the aforementioned Example 1 and are not described in detail here.

[0119] PVDF coated diaphragm refers to a diaphragm made by coating polyvinylidene fluoride (PVDF) on a commercial polyethylene diaphragm, which also includes a ceramic coating.

[0120] Comparative Example 3: This comparative example provides a coating glue solution, and the specific preparation method includes: 1. Dissolve 5 g of sodium propargyl sulfonate (Pys) in 100 mL of deionized water to obtain a sodium propargyl sulfonate solution.

[0121] 2. Add 0.5 g of conductive carbon black into the mixed solution, ultrasonically disperse it for 2 hours, stir it for 6 hours, filter the mixed solution, wash it, and dry it to obtain the modified carbon material.

[0122] 3. Add the modified carbon material into dimethyl sulfoxide (DMSO) for dispersion, and stir under vacuum at a vacuum degree of -0.08 MPa to -0.1 MPa for 1 to 6 hours to obtain a dispersed solution of modified carbon.

[0123] The present application provides a composite diaphragm, and the specific preparation method includes: 1. The oxide electrolyte NASICON with a fast ion conductor structure was ultrasonically dispersed in dimethyl sulfoxide (DMSO) for 6 hours to prepare an oxide solid electrolyte dispersion.

[0124] 2. Dissolve polybenzimidazole (PBI) powder in the oxide solid electrolyte dispersion and stir for 24 hours to obtain a composite spinning solution.

[0125] Among them, the mass ratio of oxide solid electrolyte, polymer and organic solvent is 1%:20%:79%.

[0126] 3. The composite spinning solution was made into a membrane by electrospinning, and the composite nanofiber membrane was obtained by drying at 100°C for 24 hours. The electrospinning conditions were as follows: the micropump push speed was 1.0 m / min, the syringe needle diameter was 0.05 cm, the syringe diameter was 2 cm, the receiving roller speed was 8 m / min, the needle sweep speed was 10 cm / min, the voltage was 25 kV, the distance from the syringe needle to the receiving roller was 20 cm, and the electrospinning time was 10 hours.

[0127] The composite nanofiber membrane prepared by the above process had a porosity of 90% and a thickness of 50 μm.

[0128] 4. The coating glue liquid is evenly coated on the composite nanofiber membrane by a coating machine with a coating thickness of 4 μm, and dried at 90° C. to obtain a composite diaphragm.

[0129] A sodium ion battery provided in this comparative example is prepared using the composite diaphragm obtained above, and the specific steps are consistent with those in the aforementioned Example 1, which will not be repeated here.

[0130] It should be noted that the difference between Comparative Example 3 and Example 3 is only the difference in the material of the solid electrolyte, and the other raw materials and preparation methods are completely the same.

[0131] Compare the effect parameters of the composite membranes and sodium ion batteries prepared in Examples 1-3 and Comparative Examples 1-3, see Table 1, Table 2 and Table 3.

[0132] Table 1 Comparison of performance of composite diaphragm of example and diaphragm of comparative example 1

[0133] It should be noted that, in the above table, MD represents the thermal shrinkage rate of the diaphragm in the mechanical stretching direction, that is, the longitudinal thermal shrinkage rate, and TD represents the thermal shrinkage rate of the diaphragm perpendicular to the mechanical direction, that is, the transverse thermal stretching rate.

[0134] Thermal shrinkage refers to the rate of change of the size of the diaphragm under temperature changes, and is used to characterize the dimensional stability of the diaphragm under high temperature. On the one hand, the thermal shrinkage of the diaphragm is directly related to the safety performance of the battery. For example, when the battery temperature rises to a certain level, if the thermal shrinkage of the diaphragm is too large, it will cause the diaphragm to shrink, causing the positive and negative electrodes to contact, resulting in an internal short circuit in the battery, causing the battery to overheat or even thermal runaway, which may lead to safety accidents such as fire or explosion. On the other hand, the thermal shrinkage of the diaphragm will also affect the performance of the battery. The thermal shrinkage of the diaphragm not only determines its stability in a high temperature environment, specifically, a diaphragm with a high thermal shrinkage rate is prone to shrink and deform at high temperatures, causing changes in the internal structure of the battery, affecting the thermal stability of the battery; the thermal shrinkage of the diaphragm will also affect the cycle performance of the battery. During the charge and discharge cycle of the battery, the diaphragm will repeatedly experience temperature changes. A diaphragm with a high thermal shrinkage rate may cause instability in the internal structure of the battery and affect the cycle life of the battery. The thermal shrinkage rate of the diaphragm will also affect its pore structure and the distribution of the electrolyte, thereby affecting the migration of ions and the internal resistance of the battery. Therefore, a diaphragm with a lower thermal shrinkage rate can better maintain its pore structure, which is beneficial to the retention of the electrolyte and the transmission of ions, thereby improving the electrochemical performance of the battery.

[0135] Permeability is an indicator of the gas permeability of the diaphragm, which can indirectly reflect the permeability of ions. The above table uses the Gurley value as the evaluation standard, which refers to the time it takes for a certain volume of air to pass through a diaphragm of a specified area under a certain pressure when the diaphragm is placed in a permeability tester. The size of the Gurley value is negatively correlated with the gas permeability, that is, the smaller the Gurley value, the higher the permeability. That is, the smaller the permeability value in Table 1, the higher the permeability of the corresponding diaphragm. A diaphragm with high permeability can provide a better ion transmission channel, thereby reducing the internal resistance of the battery and improving the charging and discharging efficiency of the battery. At the same time, a diaphragm with high permeability can better maintain the distribution of the electrolyte, which has a positive impact on the performance and life of the battery.

[0136] Porosity refers to the ratio of the volume of micropores in the diaphragm to the total volume of the diaphragm. Generally, when the permeability of the diaphragm decreases, the porosity of the diaphragm will become higher. That is, the higher the porosity, the better the permeability of the diaphragm, which means that the ability of gas to pass through the diaphragm is stronger. On the other hand, an increase in porosity usually reduces the internal resistance of the battery, because more pores mean that ions can move more freely between the positive and negative electrodes, thereby reducing the resistance to ion transfer and improving the cycle performance of the battery. This is because a diaphragm with a higher porosity can better maintain the distribution of the electrolyte, which helps the battery maintain stable performance during repeated charge and discharge.

[0137] As can be seen from Table 1, the composite membranes prepared in Examples 1-3 of the present application have significantly lower air permeability values ​​compared to the commercial polyethylene membrane of Comparative Example 1 and the PVDF coated membrane of Comparative Example 2, because when the porosity of the membrane increases, it can be expected that its air permeability value will decrease, which means an improvement in air permeability. This proves that the nanofiber membrane prepared by electrospinning has the characteristics of high porosity, thereby improving the air permeability of the composite membrane; and it may also have a positive impact on reducing battery internal resistance, improving battery cycle performance, and improving battery charge and discharge stability.

[0138] The composite diaphragms prepared in Examples 1-3 of the present application have significantly reduced thermal shrinkage compared to Comparative Examples 1-2, indicating that the composite diaphragms prepared in the examples of the present application have excellent stability in high temperature environments, proving that the modified carbon material introduced into the coating glue solution adopted in the present application can utilize the heat dissipation of the carbon material to disperse the heat in time and improve the safety of the battery cell; further, compared with the composite diaphragm prepared in Example 3 of the present application and the composite diaphragm prepared in Comparative Example 3, it is proved that the addition of sulfide solid electrolyte as an inorganic filler to the polymer matrix greatly improves the thermal deformation temperature of the diaphragm. Therefore, the introduction of modified carbon materials in the coating of the composite diaphragm and the use of sulfide solid electrolyte as an inorganic filler added to the polymer matrix both play an important role in improving the thermal shrinkage rate. The improvement of thermal shrinkage performance not only helps to improve the safety performance of the battery, but also helps to improve the battery performance such as thermal stability and cycle life of the battery.

[0139] Table 2 Performance comparison of composite diaphragm of example and diaphragm of comparative example 2

[0140] The test method for the above peel strength is: The positive electrode sheet, the composite separator of the embodiment or the separator of the comparative example, and the negative electrode sheet are stacked in order, the pressure is 7t, the temperature is 90℃, and the hot pressing is performed for 60s to obtain the sample, and the peel strength test is performed for comparison. The larger the peel strength value, the more difficult it is to peel, that is, the greater the bonding force.

[0141] It can be seen from Table 2 that the composite diaphragms prepared in Examples 1-3 of the present application have significantly improved peel strength compared with the diaphragm of Comparative Example 1, which means that the adhesion is significantly improved. This shows that the composite diaphragms prepared in the present application contain PVDF in the diaphragm coating, which can increase the adhesion between the diaphragm and the positive and negative electrodes, improve flexibility, and enhance the bonding effect.

[0142] Table 3 Performance comparison of sodium ion batteries prepared in the examples and comparative examples

[0143] As shown in Table 3, the sodium ion batteries prepared in Examples 1-3 of the present application have significantly lower AC resistance and 5C discharge temperature rise than those prepared in Comparative Examples 1-2, which shows that the present application uses sodium propargyl sulfonate (Pys) to modify carbon materials for coating glue, and then for the diaphragm coating of sodium ion batteries. The good conductivity and heat dissipation of carbon materials can form a conductive network on the diaphragm surface, thereby promoting electron transport in sodium ion batteries, reducing the interface reaction resistance of the battery cell, and reducing the temperature rise of the battery cell. At the same time, by physically adsorbing and coating organic sulfonates on the surface of carbon materials, the agglomeration effect of carbon materials is improved, so that a very small amount of carbon materials are evenly loaded on the surface of the diaphragm, avoiding the uneven distribution of the load on the surface of the diaphragm caused by the agglomerated carbon materials, thereby causing local charge differences, affecting cycle performance, and increasing impedance.

[0144] Compared with the sodium ion batteries prepared in Comparative Examples 1-2, the sodium ion batteries prepared in Examples 1-3 of the present application have significantly improved 5C discharge capacity retention rate and capacity retention rate after 1000 cycles, proving that the present application examples construct composite nanofiber membranes through electrospinning, and the fiber membranes prepared by electrospinning have large porosity, which is conducive to the passage of sodium ions. The high ionic conductivity of the sulfide solid electrolyte itself is used to reduce the polarization internal resistance of the battery cell and increase the cycle life of the battery cell.

[0145] The sodium ion batteries prepared in Examples 1-3 of the present application have a significantly improved liquid retention coefficient compared to the sodium ion batteries prepared in Comparative Examples 1-2, proving that the composite diaphragm of the sodium electronic battery used in the present application contains PVDF, which has good wettability and moisture retention to the electrolyte. At the same time, the sulfide solid electrolyte and cyclic carbonate in the composite diaphragm have good wettability and ionic conductivity, which can improve the overall ionic conductivity and liquid retention capacity of the diaphragm. The diaphragm of Comparative Examples 1-2 uses the diaphragm in the prior art to prepare sodium ion batteries, does not modify the coating glue, and does not use sulfide solid electrolyte to add to the composite spinning solution to prepare a composite diaphragm for sodium ion batteries. Therefore, the performance in the peel strength test, AC internal resistance, 5C discharge capacity retention rate, and capacity retention rate after 1000 cycles is inferior to the performance of the effect parameters of Examples 1-3 of the present application.

[0146] Furthermore, compared with the composite diaphragm and sodium ion battery prepared in Comparative Example 3, the internal resistance of the composite diaphragm and the sodium ion battery prepared in Example 3 is significantly reduced, and the 5C discharge capacity retention rate, the liquid retention coefficient and the capacity retention rate after 1000 cycles are significantly improved, which shows that the advantage of introducing the sulfide solid electrolyte into the composite diaphragm and then into the sodium ion battery is to utilize the high ionic conductivity of the sulfide solid electrolyte itself, reduce the polarization internal resistance of the battery cell and increase the cycle life of the battery cell. At the same time, the sulfide solid electrolyte has good wettability with cyclic carbonate and has ionic conductivity itself, which can improve the overall ionic conductivity and liquid retention capacity of the diaphragm.

[0147] In summary, the composite diaphragm prepared in the embodiment of the present application has a larger porosity than the comparative example, is more resistant to high temperatures, and has better liquid absorption and liquid retention properties; the sodium ion battery prepared in the embodiment of the present application has a smaller internal resistance than the comparative example, a higher 5C discharge capacity retention rate, a smaller 5C discharge temperature rise, and a higher capacity retention rate after 1000 cycles, that is, it has the advantages of high safety and good cycle performance, and is suitable for high-rate battery application scenarios.

[0148] The various embodiments in this specification are described in a progressive manner, and the same or similar parts between the various embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.

[0149] It should be noted that all the features recorded in the present invention (including technical features recorded in different embodiments) can be combined arbitrarily under reasonable circumstances, and new technical solutions formed by the combination are all within the protection scope of the present invention.

[0150] What is described above are only some embodiments of the present invention and are not intended to limit the present invention. Those skilled in the art should understand that the present invention may be subject to various changes and improvements, and any modifications, equivalent substitutions and improvements made in accordance with the present invention shall fall within the scope of protection required by the present invention.

Claims

1. A coating glue solution, characterized in that: The coating glue solution comprises: 3% to 5% by weight of modified carbon material, 75% to 85% by weight of organic solvent, and 10% to 22% by weight of polyvinylidene fluoride; The modified carbon material is prepared by coating sodium propargyl sulfonate on the surface of a carbon material. In the modified carbon material, the mass ratio of the carbon material to the sodium propargyl sulfonate is (0.2-0.5):(2-5).

2. The coating glue according to claim 1, characterized in that: The carbon material includes one or more of multi-walled carbon nanotubes, graphene, and conductive carbon black.

3. The coating glue according to claim 1, characterized in that: The organic solvent is any one of N-methylpyrrolidone, N,N-dimethylformamide and dimethyl sulfoxide.

4. A method for preparing a coating glue solution as claimed in any one of claims 1 to 3, characterized in that: The preparation method comprises: Dissolving 2 g to 5 g of sodium propargyl sulfonate in a preset volume of deionized water to obtain a sodium propargyl sulfonate solution; Adding 0.2 g to 0.5 g of carbon material to the sodium propargyl sulfonate solution, dispersing and stirring to obtain a mixed solution, filtering, washing and drying the mixed solution to obtain a modified carbon material; Adding the modified carbon material into an organic solvent, dispersing and stirring to obtain a modified carbon dispersion solution; Add polyvinylidene fluoride into the dispersed solution of the modified carbon, and stir to obtain the coating glue solution.

5. A composite diaphragm, characterized in that: The composite diaphragm comprises a composite nanofiber membrane and a diaphragm coating coated on at least one side of the composite nanofiber membrane; The composite nanofiber membrane is obtained by subjecting a sulfide solid electrolyte and a polymer to a membrane-forming treatment; The diaphragm coating is obtained by coating the coating glue solution according to any one of claims 1 to 3, and the thickness of the diaphragm coating is 2 μm to 4 μm.

6. A method for preparing a composite diaphragm according to claim 5, characterized in that: The method comprises: adding a sulfide solid electrolyte into an organic solvent and dispersing the sulfide solid electrolyte to obtain a sulfide solid electrolyte dispersion; adding a polymer into the sulfide solid electrolyte dispersion, and stirring to obtain a composite spinning solution; Performing film-forming treatment on the composite spinning solution by electrostatic spinning, and obtaining a composite nanofiber membrane after drying treatment; The composite nanofiber membrane is coated with the adhesive solution as described in claims 1 to 3 on at least one side of the composite nanofiber membrane, and then dried to obtain the composite membrane.

7. The method for preparing a composite diaphragm according to claim 6, characterized in that: In the composite spinning solution, the mass proportion of the sulfide solid electrolyte is 3% to 5%, the mass proportion of the organic solvent is 75% to 85%, and the mass proportion of the polymer is 10% to 22%.

8. The method for preparing a composite diaphragm according to claim 6, characterized in that: The sulfide solid electrolyte is Na3PS4, Na 11 Sn2PS2, Na3SbS4, Na 11.5 Sn2Sb 0.5 Ti 0.5 S 12 、Na 2.95 Sb 0.95 W 0.05 S 3.9 O 0.1 At least one of the following; the diameter of the sulfide solid electrolyte is 300nm to 500nm.

9. The method for preparing a composite diaphragm according to claim 6, characterized in that: The polymer is one of polyethersulfone, polyetherketone, polyethylene terephthalate, polyamide, polyvinylidene fluoride, polybenzimidazole, polyphenylene sulfide and polyimide.

10. The method for preparing a composite diaphragm according to claim 6, characterized in that: The organic solvent is any one of N-methylpyrrolidone, N,N-dimethylformamide and dimethyl sulfoxide.

11. The method for preparing a composite diaphragm according to claim 6, characterized in that: The composite nanofiber membrane has a porosity of 70% to 90% and a thickness of 10 μm to 50 μm.

12. A sodium ion battery, characterized in that: The sodium ion battery comprises the composite separator as claimed in claim 5.

Citation Information

Patent Citations

  • Efficient calcium slurry dispersant and preparation method thereof

    CN103468028A

  • Method for synchronously reducing and modifying graphene oxide

    CN103641109A